Physiotherapy Practices Regarding Osteoarthritis Management: A Recent Update - Usha; Baldev Negi; Mayank Shukla; Sumedha Rabra; Preeti Saini (Disease and Health: Research Developments Vol. 10, 2025)
Background: Osteoarthritis (OA) is a common type of arthritis affecting the adult population. In osteoarthritis, the cartilage of the associated bones gradually diminishes with the advancement of age. It is a degenerative disease that leads to a gradual decline in function, increases discomfort, and causes limitation in one’s ability to participate in the activities of daily living. Physiotherapists play a crucial role in the management of osteoarthritis. Objective: The main objective of this chapter was to summarize the findings of the knowledge, attitudes and practices regarding osteoarthritis among the physiotherapists. Methodology: In this study, 65 physiotherapists from Palwal, Faridabad and Mathura districts participated and they were provided with a KAP (Knowledge, Attitudes and Practices) questionnaire. The questionnaire was made up of the following components: informed consent, demographic details (Name, Age, Gender, Level of Education, Affiliated institution and total industrial experience in years), Knowledge questions, attitudes questions and questions related to their practices. Their responses were collected and statistically analyzed. Results and Conclusion: The results of the present KAP study found that there is diversity in the treatment methods followed by the physiotherapists besides being educated regarding osteoarthritis. This study concluded that continuing education programs were needed to fill the evidence-practice gap existing amongst the physiotherapy practitioners’ community in order to provide standardized well-established protocol to patients suffering from osteoarthritis. The result of the present study also indicates that the most common method of evaluation during the initial visit of physiotherapy by osteoarthritis patients was palpation and the most common treatment method used by the physiotherapists was aerobic exercise. In conclusion, This study reveals the awareness of physiotherapists regarding the main treatment for patients with early osteoarthritis of the knee joint. Clinical Implication: This study would be helpful in evaluating the knowledge, attitudes and practices regarding osteoarthritis among physiotherapists. Physiotherapy plays an important role in the management of an individual suffering from osteoarthritis.